2007
DOI: 10.1038/sj.bjp.0707297
|View full text |Cite
|
Sign up to set email alerts
|

Combined pharmacological block of IKr and IKs increases short‐term QT interval variability and provokes torsades de pointes

Abstract: Background and purpose: Assessing the proarrhythmic potential of compounds during drug development is essential. However, reliable prediction of drug-induced torsades de pointes arrhythmia (TdP) remains elusive. Along with QT interval prolongation, assessment of the short-term variability of the QT interval (STV(QT)) may be a good predictor of TdP. We investigated the relative importance of I Ks and I Kr block in development of TdP together with correlations between QTc interval, QT interval variability and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
116
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(126 citation statements)
references
References 38 publications
8
116
0
2
Order By: Relevance
“…Therefore, in absence of relevant human cellular electrophysiological data, canine ventricular myocytes were chosen to analyze experimentally the determinants of SV in the present study due to two reasons. (1) Canine ventricular myocytes are believed to resemble human ventricular cells regarding their action potential morphology and kinetics of the underlying ion currents [19,20]; and (2) a large mass of in vitro and in vivo experimental data on beat-to-beat variability have been obtained in this species [1,12,13,15,22,23]. Here is to be mentioned that all action potentials analyzed in the present study were normally driven ones, records taken in myocytes displaying early or delayed afterdepolarizations were excluded from evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in absence of relevant human cellular electrophysiological data, canine ventricular myocytes were chosen to analyze experimentally the determinants of SV in the present study due to two reasons. (1) Canine ventricular myocytes are believed to resemble human ventricular cells regarding their action potential morphology and kinetics of the underlying ion currents [19,20]; and (2) a large mass of in vitro and in vivo experimental data on beat-to-beat variability have been obtained in this species [1,12,13,15,22,23]. Here is to be mentioned that all action potentials analyzed in the present study were normally driven ones, records taken in myocytes displaying early or delayed afterdepolarizations were excluded from evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with this, Lengyel et al. found that the beat-to-beat variability of the QT interval predicted the occurrence of druginduced TdP in anaesthetized rabbits 68 . In contrast, the beat-to-beat variability of the QT interval failed to predict repolarization-prolonging-drug-induced TdP in two recent investigations with adrenergically stimulated, anaesthetized rabbits 27,69 .…”
Section: The Applied Repolarization Related Biomarkers Did Not Correlmentioning
confidence: 66%
“…It has been shown that beatto-beat variability of the repolarization measured in regular rhythm predicted TdP in clinical 24 and experimental 16,25,26 settings. However, beat-to-beat variability of repolarization measured in regular rhythm did not predict drug-induced TdP in anaesthetized rabbits [27][28][29][30] and guinea pigs 31 .…”
Section: Biomarkers In Prediction Of Torsades De Pointesmentioning
confidence: 99%
See 2 more Smart Citations